2011
DOI: 10.1002/joc.2071
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the sensible heat and momentum transfer coefficients over the Gobi in Northwest China

Abstract: Utilizing the data of the intensive observation period (May-June 2000) of the Dunhuang land-surface process field experiment supported by the 'Atmosphere-land Interactive Field Experiment over Arid Regions of Northwest China(NWC-ALIEX)', the bulk momentum transfer coefficient (C d ) and the bulk sensible heat transfer coefficient (C h ) between the surface and the atmosphere over the arid Gobi Desert region are determined using three different methods. The results indicate that these coefficients, especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The neutral bulk transfer coefficient for heat C HN can be related to the roughness length scales for heat ( z oh ) and momentum ( z om ) via [ Zhang et al ., ]: CHN =κ2lntrue(zref zom true)lntrue(zref zoh true), where κ ≈ 0.4 is the von Karman constant and z ref is the height of micrometeorological measurement.…”
Section: Strong‐constraint Vda Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neutral bulk transfer coefficient for heat C HN can be related to the roughness length scales for heat ( z oh ) and momentum ( z om ) via [ Zhang et al ., ]: CHN =κ2lntrue(zref zom true)lntrue(zref zoh true), where κ ≈ 0.4 is the von Karman constant and z ref is the height of micrometeorological measurement.…”
Section: Strong‐constraint Vda Resultsmentioning
confidence: 99%
“…The roughness length scales for heat and momentum are themselves related through κB −1 =ln ( z om / z oh ), where B is the Stanton number [ Brutsaert , ; Yang and Friedl , ; Zhang et al ., ]. Brutsaert [] and Duynkerke [] showed the dependence of κB −1 on LAI and friction velocity.…”
Section: Strong‐constraint Vda Resultsmentioning
confidence: 99%
“…It combines the aerodynamic method with the energy balance method and determines the turbulent fluxes in the surface layer by using the universal functions of the M‐O similarities and the surface‐energy balance equation. Previous studies have evaluated this method and indicated that it is feasible in the Northwest China (Hu & Qi, ; Ma & Ma, , ; Zhang et al, ), where there are few observation sites. The H and ET determined by the combinatory method, which calculates the turbulent flux using the surface layer gradient measurements, were treated as the actual values and were used for the validation of the model estimations.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The bulk heat transfer coefficient (C H ) can be written as the product of the neutral bulk heat transfer coefficient (C HN ) and a correction function for atmospheric stability, f(Ri) (i.e., C H = C HN f(Ri), where Ri is the Richardson number). C HN can be related to roughness length scales for heat and momentum [Liu et al, 2007b;Zhang et al, 2010], which is mainly a function of vegetation phenology and is assumed to vary on a monthly temporal scale [McNaughton and Van den Hurk, 1995;Jensen and Hummelshøj, 1995;Qualls and Brutsaert, 1996;Crow and Kustas, 2005;Bateni et al, 2013b]. It scales the sum of turbulent heat fluxes (H + LE) and constitutes the first unknown parameter of the CS scheme.…”
Section: Surface Energy Balance (Seb)mentioning
confidence: 99%